Nucleic acid amplification-based methods for microRNA detection. Issue 6 (26th February 2015) - Chen, Hui-Ling; Guo, Meng-Meng; Tang, Hao; Wu, Zhan; Tang, Li-Juan; Yu, Ru-Qin; Jiang, Jian-Hui
Abstract : This review traces the basic principles of several nucleic acid amplification-based microRNA detection methods that have been developed in recent three years. Abstract : MicroRNAs (miRNAs) are quite short single-stranded RNA molecules playing crucial roles in many biological processes and recognized as potential diagnostic biomarkers as well as targets for drug discovery in cancers. It has fueled a great need for the development of highly sensitive and selective detection methods for miRNAs. Many nucleic acid amplification technologies are demonstrated methods which have exhibited great potential for the development of simple, sensitive, specific and high-throughput methods for the detection of miRNA. Herein, we review the basic principles of five types of nucleic acid amplification-based miRNA assay methods that have been established in recent three years. Sensitive miRNA detection based on polymerase chain reaction, rolling circle amplification, strand displacement amplification, duplex-specific nuclease signal amplification, and hybridization chain reaction techniques is discussed.